Membangun Kesadaran Ekologis di Era Digital: Eksplorasi Filsafat Nilai Max Scheler dalam Konten Pandawara Group: Building Ecological Awareness in the Digital Age: Exploring Max Scheler's Philosophy of Values ​​in Pandawara Group Content - Dony, Ahmad Rama (Undiksha, 2024)
The serious problem of waste has become a major catalyst in the current global environmental crisis. This challenge has prompted various groups to formulate concrete solutions to deal with the negative impacts of suboptimal waste management. In the digital era, the link between value philosophy and digital content is becoming increasingly important. Digital content, especially those spread through social media, contains values that require in-depth exploration to understand its ethical implications for the transformation of the mindset and behavior of the wider community. This study aims to find and describe the values present in the action and publication of waste management content by Pandawara Group from the perspective of Max Scheler's philosophy of value. The method used is qualitative research with a descriptive analysis approach. The results of this study illustrate a number of values reflected in the action and publication of Pandawara Group's content related to waste management. First, the emergence of happiness value, which is found in the positive impact felt by media users in general when interacting with Pandawara Group's content. Secondly, there is the emergence of vital value, which is reflected in efforts to reawaken awareness of public welfare and health. Third, there is an evocation of spiritual concern for the surrounding environment for social media users by showing the link between the spiritual dimension and environmental preservation. Finally, at the highest stage, the emergence of sacred values, which are reflected in respect for the rights of nature that must be preserved. Pandawara Group has transformed into an entity that not only acts as an agent of change, but also has a significant positive impact in creating values of awareness, wisdom, and prosperity among the community in an effort to preserve the environment.